Study on Primary Fish Species in Lake Ogii: Catch-Related Injuries and Hygiene Practices (Mongolian Journal of Agricultural Sciences, 2024)
Mongolia’s rivers and lakes host over 70 fish species, with approximately 30 species harvested for human consumption. The annual fishing season typically spans 180 days, yielding an estimated 600 tons of fish annually. Fishing in Ogii Lake, Arkhangai Province, began in 1938; however, recent years have seen a cessation of regulated fishing, alongside a rise in large-scale illegal fishing, particularly during winter and spawning periods. Climate change has further impacted aquatic ecosystems by altering water regimes, increasing pollution, degrading habitats, and disrupting fish reproductive cycles, resulting in ecological imbalance.This study collected fish samples over three years at seasonal intervals from two to three subsistence fishing households on Ogii Lake. The species composition identified included Perch (Perca fluviatilis), Ide (Leuciscus idus), Roach (Rutilus rutilus), and Northern Pike (Esox lucius). A total of 1,567 fish from these four species were caught using control nets, with sensory and laboratory analyses conducted in 3–5 replicates. The findings highlight the urgent need for standardized protocols in fishing, transport, processing, and storage to promote fishery sustainability and product quality.